Thermally induced cationic polymerization of glycidyl phenyl ether using novel xanthenyl phosphonium salts - Gupta, Mukesh Kumar; Singh, Raj Pal (Macromolecular Research, 2009)
The present study firstly describes the synthesis of novel, thermo-latent initiators based on xanthenyl phosphonium salts with different counter anions and phosphine moieties and secondly examines their efficiency in the bulk polymerization of glycidyl phenyl ether (GPE). The polymerization was performed with phosphonium salt initiators (I(SbF6), I(PF6), I(AsF6) and I(BF4)) at ambient temperature to 200 degrees C for 1 h. The order of initiator activity was I(SbF6) > I(PF6) > I(AsF6) > I(BF4). To examine the effect of the phosphine moiety on the initiator activity, polymerization was carried out with I(SbF6) (Ph(3)P) and II(SbF6) (Bu(3)P) at ambient temperature to 170 degrees C for 1 h. The order of reactivity was I(SbF6) > II(SbF6). In general, the conversion percentage increased with increasing polymerization temperature. The thermal stability of these salts was measured by then-no gravimetric analysis (TGA). The solubility of phosphonium salts in various organic solvents and epoxy monomers was also investigated.
Keywords: Cationic polymerization; glycidyl phenyl ether; phosphonium salts; thermo-latent